Validation of Freshly Isolated Rat Renal Cells as a Tool for Preclinical Assessment of Radiolabeled Receptor-Specific Peptide Uptake in the Kidney - Barta, Pavel; Nachtigal, Petr; Maixnerova, Jana; Zemankova, Lenka; Trejtnar, Frantisek (Pharmaceuticals (Basel, Switzerland), 2023)
The synthetic analogs of regulatory peptides radiolabeled with adequate radionuclides are perspective tools in nuclear medicine. However, undesirable uptake and retention in the kidney limit their application. Specific in vitro methods are used to evaluate undesirable renal accumulation. Therefore, we investigated the usefulness of freshly isolated rat renal cells for evaluating renal cellular uptake of receptor-specific peptide analogs. Special attention was given to megalin as this transport system is an important contributor to the active renal uptake of the peptides. Freshly isolated renal cells were obtained from native rat kidneys by the collagenase method. Compounds with known accumulation in renal cells were used to verify the viability of cellular transport systems. Megalin expressions in isolated rat renal cells were compared to two other potential renal cell models by Western blotting. Specific tubular cell markers were used to confirm the presence of proximal tubular cells expressing megalin in isolated rat renal cell preparations by immunohistochemistry. Colocalization experiments on isolated rat kidney cells confirmed the presence of proximal tubular cells bearing megalin in preparations. The applicability of the method was tested by an accumulation study with several analogs of somatostatin and gastrin labeled with indium-111 or lutetium-177. Therefore, isolated rat renal cells may be an effective screening tool for in vitro analyses of renal uptake and comparative renal accumulation studies of radiolabeled peptides or other radiolabeled compounds with potential nephrotoxicity.
Keywords: megalin; radiotoxicity; radiopeptide; nephrotoxicity; renal retention; cellular model